2016
DOI: 10.1002/acr.22715
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Composition and Hormonal and Inflammatory Factors With Tibial Cartilage Volume and Sex Difference in Cartilage Volume in Young Adults

Abstract: Objective. To describe the associations between body composition and hormonal and inflammatory factors measured 5 years prior and tibial cartilage volume in young adults, and to explore if these factors contribute to the sex difference in tibial cartilage volume. Methods. Subjects broadly representative of the young adult Australian population (n 5 328, ages 31-41 years, 47.3% women) were selected. They underwent T1-weighted fat-suppressed magnetic resonance imaging (MRI) of their knees. Tibial cartilage volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 38 publications
1
18
1
1
Order By: Relevance
“…Interestingly, compared to those studies on older populations 26e31 , those studying younger population found no association between weight/BMI and cartilage volume 25,32,33 . This may reflect the effects of ageing making knee joints more susceptible to body weight 38 .…”
Section: Discussioncontrasting
confidence: 58%
“…Interestingly, compared to those studies on older populations 26e31 , those studying younger population found no association between weight/BMI and cartilage volume 25,32,33 . This may reflect the effects of ageing making knee joints more susceptible to body weight 38 .…”
Section: Discussioncontrasting
confidence: 58%
“…Similarly, we did not find any significant association between overweight status in childhood and adulthood knee structures, including cartilage volume after 25 years (data not published). However, we found that lean mass in young adults was positively and fat mass was negatively associated with tibial cartilage volume in young Australian adults [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…32 There is also evidence suggesting fat-free body mass and muscle mass or muscle strength, but not BMI, is positiviely associated with cartilage thickness, while the opposite might be true for fat mass. 29,30,33,34…”
Section: Discussionmentioning
confidence: 99%